Experience with provisional WHO‐entities large B‐cell lymphoma with IRF4‐rearrangement and Burkitt‐like lymphoma with 11q aberration in paediatric patients of the NHL‐BFM group. (2nd April 2020) - Au‐Yeung, Rex K. H.; Arias Padilla, Laura; Zimmermann, Martin; Oschlies, Ilske; Siebert, Reiner; Woessmann, Wilhelm; Burkhardt, Birgit; Klapper, Wolfram
Summary: Large B‐cell lymphoma with IRF4 rearrangement, and Burkitt‐like lymphoma with 11q aberration are two provisional lymphoma entities in the 2017 revision of the WHO classification of lymphoid neoplasms. Despite being more frequent in young patients, knowledge regarding their true incidence and clinical features in unselected cohorts of paediatric and adolescent patients is limited. We screened for both entities among paediatric patients (<18 years of age) in the German NHL‐BFM (Non‐Hodgkin lymphoma Berlin‐Frankfurt‐Münster) group. Among follicular lymphomas and diffuse large B‐cell lymphomas (DLBCL), 7/34 cases (21%) showed an IRF4 break‐apart pattern by fluorescence in situ hybridisation (FISH) and are associated with stages I and II disease ( P  = 0·043). Among lymphomas morphologically resembling Burkitt lymphoma, DLBCL and high‐grade B‐cell lymphoma, unclassifiable, 13/102 cases (13%) lacked a MYC break‐apart pattern but were positive for 11q proximal gain and telomeric loss by FISH. MYC ‐negative Burkitt‐like lymphomas with the typical 11q gain‐loss pattern by FISH were older ( P  = 0·004), showed less male predominance ( P  = 0·003), lower stage ( P  = 0·040), lower serum LDH level ( P  = 0·01) and less abdominal involvement ( P  = 0·008) compared to high grade B‐cell lymphomas without 11q gain‐loss pattern. Both entities showed excellent outcome with overall survival of 100% when managed according to NHL‐BFM strategies and may provide candidates for future therapy de‐escalation in clinical trials.